2009
DOI: 10.1177/089686080902902s42
|View full text |Cite
|
Sign up to set email alerts
|

Does Immunosuppressive Treatment Ameliorate Morphology Changes in Encapsulating Peritoneal Sclerosis?

Abstract: Encapsulating peritoneal sclerosis (EPS) is a clinical syndrome associated with ileus symptoms and irreversible sclerosis of the peritoneal membrane. Inflammation, fibrosis, and neoangiogenesis are the main features of the pathophysiology. No evidence-based therapy is currently available for EPS. In recent years, anti-inflammatory and immunosuppressive (IS) treatment modalities have become more popular. The aim of the present study was to investigate the effects of various IS treatment strategies—glucocortico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…A variety of other immunosuppressive medications like azathioprine, rapamycin, mycophenalate mofetil, sirolimus, and cyclosporine have also been used to treat EPS either alone or in combination with steroids (Rajani, 2002 ; Wong et al, 2005 ; Lafrance et al, 2008 ). However, apart from steroids, evidence regarding the efficacy of any other immunosuppressive therapy in EPS remains weak due to lack of robust randomized clinical trials (Bozkurt et al, 2009 ).…”
Section: Therapeutic Management Of Epsmentioning
confidence: 99%
“…A variety of other immunosuppressive medications like azathioprine, rapamycin, mycophenalate mofetil, sirolimus, and cyclosporine have also been used to treat EPS either alone or in combination with steroids (Rajani, 2002 ; Wong et al, 2005 ; Lafrance et al, 2008 ). However, apart from steroids, evidence regarding the efficacy of any other immunosuppressive therapy in EPS remains weak due to lack of robust randomized clinical trials (Bozkurt et al, 2009 ).…”
Section: Therapeutic Management Of Epsmentioning
confidence: 99%
“…3 Some studies suppose the role of calcineurin inhibitors (CNIs) in developing or aggravating EPS. 4,5 Many of these factors play roles in up-regulation of transforming growth factor-b (TGF-b) and vascular endothelial growth factor (VEGF) and subsequent epithelial to mesenchymal transition (EMT), fibrosis and neoangiogenesis. 6,7 Treatment of EPS differs from medical therapy for lower stages to surgery for higher stages.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that after MMF treatment, MMP-2 and TGF-β1 gene expressions decreased significantly []. Moreover, sirolimus showed no significant effect on MMP-2 levels [31]. MMF and sunitinib treatment have a significant impact on dialysate TGF-β1 levels as compared with the resting EPS rat model [,].…”
Section: Discussionmentioning
confidence: 99%